2010
DOI: 10.1002/adsc.201000191
|View full text |Cite
|
Sign up to set email alerts
|

Highly Chemo‐ and Regioselective Reduction of Aromatic Nitro Compounds Catalyzed by Recyclable Copper(II) as well as Cobalt(II) Phthalocyanines

Abstract: Copper/cobalt phthalocyanines were established for the first time as catalysts for the very efficient chemo-and regioselective reduction of aromatic nitro compounds to generate the corresponding amines. The selective reduction of nitro compounds was observed in the presence of a large range of functional groups such as aldehyde, keto, acid, amide, ester, halogen, lactone, nitrile and heterocyclic functional groups. Furthermore, the present method was found to be highly regioselective towards the reduction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…Besides molybdenum-, iron-, and zinc-based systems the application of copper can be beneficial. Indeed, the potential of copper catalyst in reduction techniques has been explored in the reduction of various functionalities [46][47][48][49][50][51][52][53][54][55][56][57][58]. However, the catalytic reduction of sulfoxides in the presence of copper has been so far unreported, while the converse process has been studied [59].…”
Section: Introductionmentioning
confidence: 97%
“…Besides molybdenum-, iron-, and zinc-based systems the application of copper can be beneficial. Indeed, the potential of copper catalyst in reduction techniques has been explored in the reduction of various functionalities [46][47][48][49][50][51][52][53][54][55][56][57][58]. However, the catalytic reduction of sulfoxides in the presence of copper has been so far unreported, while the converse process has been studied [59].…”
Section: Introductionmentioning
confidence: 97%
“…[4] A crucial issue for the general application of catalysts for nitro reduction is selectivity. [7,8] Hence, a wide variety of organometallic catalysts based on Pd, [7] Ru, [7][8][9] Rh, [7] Co, [10] Cu, [10] and even Fe [11] have been described. Recently, Corma and co-workers demonstrated that Au-based catalysts show high selectivity for the reduction of the nitro arenes.…”
mentioning
confidence: 99%
“…In continuation of our work on the development of synthetic methodologies for various important organic transformations [9,[55][56][57][58][59][60], herein we report an effective watercatalyzed method for the synthesis of 2-substituted benzazoles including benzimidazoles, benzoxazoles, and benzothiazoles in water as reaction medium.…”
Section: Introductionmentioning
confidence: 99%